Interventions to improve resilience in breast cancer patients: a systematic review - Retnaningsih, Dwi; Nursalam, Nursalam; Nihayati, Hanik Endang (Intelektual Pustaka Media Utama, 2025)
Breast cancer patients with low resilience may experience adverse psychological outcomes, including stress, anxiety, depression, emotional dysregulation, and difficulties in recovery. This systematic review aims to evaluate the effectiveness of various interventions in improving resilience among breast cancer patients and to provide practical guidance for healthcare practitioners in implementing these interventions. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines and PICOS framework, a comprehensive search was conducted across PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2018-2024. Two independent reviewers screened eligible studies in two stages (title/abstract and full-text). The methodological quality of included studies was assessed using the Joanna Briggs Institute Critical Appraisal Tool. A total of 20 studies met the inclusion criteria. Interventions identified include music therapy, mindfulness, family and social support programs, cognitive behavioral therapy, digital-based interventions, and psychoeducation. Most interventions demonstrated a significant positive impact on patients’ psychological resilience, coping ability, and quality of life. Evidence suggests that resilience-focused interventions can be effectively integrated into supportive care for breast cancer patients. Healthcare practitioners should consider incorporating these strategies to address psychosocial needs. Further studies are recommended to evaluate long-term impacts and cost-effectiveness in diverse settings.